Identidade de gênero e reconhecimento : o registro do nome social no meio acadêmico (um estudo de caso na UFES) - Butkovsky Júnior, Carlos Alberto (2017)
This interdisciplinary research had as objective to know the implications of amending of the social name to transgender students at the Federal University of the Espírito Santo, in Goiabeiras campus. This way, we sought to understand how the administrative dynamics of the amending the student´s social name have been taking place from the approval of University Council Resolution - 23/2014 on, which guarantees the right to the use the social name in this Institution of Higher Education – IES spaces. It was also sought to know from the students who use this legal institute, how they have perceived respect towards their gender identity at university community spaces. Anchored in their narratives, it was possible to bring up every day academic situations related to the use of the social name, uncovered in this institution at the level of Academic Master's research until then. It is worth noting that despite the desire to broaden the sample of interviewees, researching PostGraduation students at UFES; this was not possible since there was no student with a social name registered in the database of the Office of Post Graduate Studies and Research. The research was characterized by its qualitative nature since it dealt with a reality which cannot be quantified as it responds to specific questions. It is an exploratory research because the theme required contact with new event, therefore we justify the choice of such a strand since this modality embraces researches which are close to unpublished studies, aiming to create greater familiarity with them. The semi-structured interviews were used as a tool to obtain data and after analyzing the outcome, suggestions were made to mitigate the negative results found. It is concluded with this research that for the exercise and respect towards the transgender students, a set of actions to achieve changes should be implemented to guarantee the adequate accomplishment of such demands, as well as it is interesting to reinforce the policies of inclusion of the transgender ones, promoting an embracing atmosphere for these students.